PELATIHAN BERBASIS PEMBERDAYAAN PEREMPUAN DALAM PEMANFAATAN NASI SISA MENJADI MAKANAN BERGIZI - Kusmaryono, Imam; Ubaidah, Nila; Abdul Basir, Mochamad; Wijayanti, Dyana; Maharani, Hevy Risqi; Aminudin, Mohamad (Universitas PGRI Yogyakarta, 2025)
Women, especially housewives, are agents of change within their families and communities. Therefore, women's empowerment is crucial to supporting improved family well-being. One way to empower women is through providing them with skills to process leftover rice into delicious, nutritious, and economically valuable meals. This community service activity, conducted by a team of lecturers and students from Sultan Agung Islamic University, took the form of training. Participants were housewives and young women in the Genuk sub-district of Semarang City. The training, which utilizes leftover rice to create delicious and nutritious meals, has proven effective in increasing the knowledge, skills, and awareness of Family Welfare Movement (PKK) women regarding the importance of food waste management. This activity also opens up creative business opportunities based on household food and supports sustainable women's empowerment. Keywords: women's empowerment, skills training, processing leftover rice